Efecto de la presión tributaria sobre la informalidad laboral en el departamento de Loreto periodo 2009 – 2020 - Chen Garcia, Lucy Sofia (2023)
This thesis aimed to determine the effect of tax pressure on labor informality through a linear econometric model with a Granger causality scheme. The results showed that there is a positive and significant effect of 1.73 percentage points on labor informality when tax pressure increases by 1 percentage point. This means that as tax pressure increases, so does the rate of labor informality. These results can have important implications for tax and labor policy, as they suggest that tax increases can have a negative impact on formal employment. The results also highlight the importance of finding an adequate balance between tax collection and the promotion of formal employment and the reduction of labor informality. In summary, the research provides empirical evidence on the relationship between tax pressure and labor informality, and emphasizes the need to consider these factors when designing effective fiscal and labor policies.